Perancangan - Toto Rianto; Karyadi; Rini Suwartika (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
Petty cash management is an important element in a company's finances, especially for Enno Tour & Travel which has high daily transactions. Inaccurate recording of petty cash can result in cash leakage and affect the company's financial health. This research formulates problems related to challenges in managing petty cash manually and how a web-based accounting information system can overcome these problems. The purpose of this research is to design and implement an accounting information system that can improve the efficiency and accuracy of petty cash recording. The research method used is software engineering with a waterfall approach, which includes requirements analysis, system design, implementation, and testing. Data was collected through interviews and direct observation at Enno Tour & Travel. The results showed that the developed system can record petty cash transactions in real time, produce accurate financial reports, and increase transparency and accountability. Users reported increased efficiency and reduced recording errors. This study concludes that the designed web-based accounting information system improves efficiency and accuracy in petty cash management and positively contributes to the company's overall financial management.